2005
DOI: 10.1158/1078-0432.ccr-05-0683
|View full text |Cite
|
Sign up to set email alerts
|

Novel Genes Associated with Malignant Melanoma but not Benign Melanocytic Lesions

Abstract: Purpose: Cutaneous melanoma is a common, aggressive cancer with increasing incidence. The identification of melanoma-specific deregulated genes could provide molecular markers for lymph node staging assays and further insight into melanoma tumorigenesis. Experimental Design:Total RNA isolated from 45 primary melanoma,18 benign skin nevi, and 7 normal skin tissue specimens were analyzed on an Affymetrix Hu133A microarray containing 22,000 probe sets. Results: Hierarchical clustering revealed a distinct separati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

26
444
3
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 473 publications
(474 citation statements)
references
References 30 publications
26
444
3
1
Order By: Relevance
“…The L1CAM homolog gene expression pattern in our study was inconsistent with a previous study of melanomas and nevi that used frozen tissue on DNA microarray and reported increased L1CAM expression in melanoma compared to nevi. 12 The discrepancy may relate to our study of a L1CAM homolog, rather than the L1CAM examined in the prior study. Previous studies reported relatively similar expression levels of HLA (MHC class I) genes in melanoma and nevi 11 whereas we found higher expression of HLA-A and HLA-B (MHC class I) genes in melanoma relative to nevi (Figure 3a).…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…The L1CAM homolog gene expression pattern in our study was inconsistent with a previous study of melanomas and nevi that used frozen tissue on DNA microarray and reported increased L1CAM expression in melanoma compared to nevi. 12 The discrepancy may relate to our study of a L1CAM homolog, rather than the L1CAM examined in the prior study. Previous studies reported relatively similar expression levels of HLA (MHC class I) genes in melanoma and nevi 11 whereas we found higher expression of HLA-A and HLA-B (MHC class I) genes in melanoma relative to nevi (Figure 3a).…”
Section: Discussionmentioning
confidence: 74%
“…Previous DNA microarray studies of melanocytic lesions used frozen tissue and did not employ laser capture microdissection. [9][10][11][12][13]16 In this study, arrays were processed in two groups; the initial 120 cases and a 'blind' group of 45. As slight variations in array data between different lots can artificially bias the results of an unsupervised clustering study, tissues from primary cutaneous melanomas and nevi from the first 86-sample subset were subjected to unsupervised hierarchical clustering which identified two separate and distinctive groups of lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Five different datasets were included for several major cancer types, in particular breast carcinoma (TCGA consortium), 3134 colorectal carcinoma (http://www.intgen.org or TCGA consortium), 35,36 non-small cell lung carcinoma (TCGA consortium) 3740 and melanoma, 4145 to study the correlation between the expression level of metagenes indicating the presence of immune cell types and a variety of chemotactic factors and receptors. An extra dataset concerning breast carcinoma 46 was used for studying expression variability and treatment response.…”
Section: Resultsmentioning
confidence: 99%
“…Others, using cell lines or tissue samples, have studied DNA expression profiling of normal melanocytes, nevi, primary melanomas, and regional and distant metastases. [7][8][9][10][11][12][13][14][15][16][17][18][19] Conway et al 19 used the cDNA-mediated annealing, selection, extension, and ligation assay to evaluate formalin-fixed, paraffin-embedded archival primary melanoma specimens, and reported osteopontin overexpression as a potential prognostic biomarker. Rangel et al, 20 using immunohistochemistry, had previously shown that overexpression of osteopontin, correlated with the likelihood of sentinel lymph node metastasis.…”
mentioning
confidence: 99%